Reorientasi Dikotomis Ilmu Agama dan Umum: Studi Perguruan Tinggi - Hamdi; Rambli (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This research seeks to provide a comprehensive analysis of the reorientation of the dichotomy between religious and general sciences within higher education. The main objective is to investigate how integration practices have been conceptualized and implemented, while also offering policy recommendations that may serve as the foundation for a more holistic and future-oriented curriculum. The study adopts a qualitative approach with a literature review design, employing Miles and Huberman’s interactive analysis model, which involves the processes of data collection, reduction, presentation, and conclusion drawing. Through this framework, the researcher critically examines various perspectives and findings from previous studies related to the integration of knowledge. The results indicate that higher education institutions should not only focus on advancing disciplinary excellence but also prioritize the interconnection of religious and general sciences to produce graduates with balanced intellectual capacity and moral integrity. Furthermore, this reorientation contributes significantly to building an inclusive educational atmosphere that embraces diversity and interdisciplinarity. Achieving this vision requires strong collaboration among educators, academic institutions, and government agencies to ensure sustainable educational transformation and to strengthen the role of higher education as a driver of social and cultural progress.